Implementing Pancasila Philosophy in Early Childhood Education: An Indonesian Educational Model Study - Maesaroh Lubis Lubis (Yayasan Cerdas Pedia Indonesia, 2026)
This study examines the philosophical transformation of early childhood education in the smart pedagogy era through ontological, epistemological, and axiological analysis of the Merdeka curriculum based on Pancasila. Smart technology disruptions and globalization dynamics demand a recalibration of the educational system that does not merely focus on technological proficiency, but also on moral character resilience. Using a qualitative integrative literature review method, this research confronts the Western materialism framework with Pancasila philosophy. The results indicate that ontologically, Pancasila positions children as monopluralist entities with sacred purity. Epistemologically, knowledge transmission is realized through backward learning design based on dialectical inquiry, subordinating digital instruments under strict pedagogical control. Axiologically, this technological innovation must be calibrated to manifest the Pancasila Student Profile as a defense mechanism against the social degradation of contemporary cyber civilization. Conclusively, harmonious synergy between noble Pancasila values and smart pedagogy innovation constitutes an absolute prerequisite to sculpt superior character.